Lista de las aves de la Provincia de Santa Fe - MARTINEZ ACHENBACH, Guillermo (MINISTERIO DE EDUCACION Y CULTURA, 1957)
Contenido : ÑANDU; AVESTRUZ; MARTINETA; PERDIZ; MONTARAZ; MACAES; VIGUAES; GARZAS; MIRASOLES; HOCOES; CIGÜEÑAS; BANDURRIAS; GANSO; GUACAMAYO; CHAJA; CISNE; PATOS; URUTAU; PALOMAS; TORCAZAS; MARTIN-PESCADORES; CRESPIN; PIRINCHOS; GALLITO DE LA ISLA; TEROS; GAVIOTAS; CUERVOS; AGUILAS; HALCONES; CHIMANGOS; CARANCHO; PAVA DE MONTE; CHARATA; MITU; GALINETA; LECHUZAS; LOROS; PICAFLORES; CARPINTEROS; ÑACURUTU; CABURE; COTORRAS; COPETONA